Effects of a weighted club warm-up on golfing performance and biomechanics - Wardell, G. (2019)
Increasing financial incentives associated with tournament results in golf has led to players, coaches,and sport scientists researching different methods of enhancing performance, especially for the long game (> 91.44 m or 100 yards). Indeed, golfing performance has become increasingly reliant onlong game performancedue to developments in technology, equipment, physical preparation,and golf swing biomechanics. Golfers are using a variety of warm-up strategies to improve driving performance, including the use of weighted equipment. SuperSpeed Golf™ incorporates the use of differing weighted clubs in a golf-specific warm-up, claiming to enhance clubhead speedfor up to 30 minutes post use. SuperSpeed Golf™ asserts that over 600 Professional Golfers Association (PGA) players are currently using the product. Although post activation potentiation and overspeed training literature is cited in support of the use of weighted implements in ball striking sports, there is currently a lack of scientific evidence to substantiate the enhancement in performance from using the SuperSpeed Golf™ clubs and recommended warm-up protocol. Therefore, the aims of this Thesis were to: (1)systematically review and quality appraise articles addressing golf and 3D biomechanics (Chapter One); (2) systematically review and quality appraise articles addressing weighted equipment used during warm-ups for ball striking sports (Chapter Two); (3) investigate the acute effects of using the SuperSpeed clubs and recommended warm-up protocol on golf driving performance and biomechanics (Chapter Three); and (4) investigate the persistence of the effects of the SuperSpeed warm-up protocol on clubhead, ball, and swing biomechanics during a simulated golf tournament scenario (Chapter Four). As part of the systematic review in Chapter One, 23articles on golf and 3D biomechanics in professional or high level amateurs (handicap < 5.0) were assessed for their methodological quality, with only two articlesachieving a strong quality score based on the Effective Public Health Practice Project (EPHPP) quality assessment tool. From the reviewed studies, the biomechanical measures most consistently reported to relate to clubhead and ball speed were pelvis and torso axial rotation, pelvis and torso rotational velocity, X-factor,and X-factor stretch. As part of the systematic review in Chapter Two, seven articles on weighted equipment used during warm-ups for ball striking sports were assessed for their methodological quality, with only one article achieving a strong quality score based on the EPHPPquality assessment tool. All articles meeting inclusion addressed the sport of baseball. From the reviewed studies, the use of weighted equipment as a means to enhance subsequent swing performance in baseball was either ineffective or detrimental. The lack of research in ball striking sports outside of baseball and the generally weak quality of articles in the area highlight the need for better quality studies in different ball striking sports. Based on the current systematic review findings, there is limited evidence to substantiate the use of weighted equipment in golf as means to enhance subsequent performance. In Chapter Three, 12 (7 males, 5 females) high level amateurs (handicap < 3.0) completed a golf-specific control and weighted club (SuperSpeed Golf™) warm-up protocol followed by 5 swings using their own driver assessed using 3D motion analysis (500 Hz, Qualisys AB, Sweden). Swing, angular velocity, X-factor,and centre of mass (COM) parameters were extracted and compared between warm-up conditions using Cohen`s standardised effect size (ES). The SuperSpeed warm-up protocol led to significant (p< 0.05) small(ES > 0.2) and likely (greater than 75% likelihood) changes in clubhead speed(2.6 mphfaster), angular velocity of the torso (18.2 °/sfaster) and lead arm(36.0 °/sfaster), and COM position at the top of backswing in the xdirection (0.59 cm closer to the target) and at impact in the y direction (0.34 cm more to the left of the target). However, no significant change was seen in ball speed, leading to a significant moderateand likely negative change in smash factor (-0.3 clubhead speed to ball speedratio), suggesting that the increased clubhead speedwas not efficiently transferred to the ball at impact.In Chapter Four, the same 12 (7 males, 5 females) high level amateurs(handicap < 3.0) completed five sets of five swings walking 400 m between sets under the two randomised warm-up conditions (golf-specific control and SuperSpeed). The persistence of any meaningful effects detected in the initial set was assessed across sequential sets. The significant small and likely changes in clubhead speed, smash factor, angular velocity of the torso and lead arm, and two COM variables subsequent the SuperSpeed warm-up compared to the control warm-up in the initial setwere no longer meaningfulfrom the second set onward after walking the distance of a simulated golf hole. These findings suggest that the SuperSpeed warm-up protocol performed pre-tournament does not meaningfully improve golfing performance in a golf-specific context from the second hole onwards. Results from the two systematic reviews highlight the need for betterquality methodological studies in golf biomechanics and use of weighted implements in ball striking sports. From the golf biomechanics literature reviewed, pelvis and torso axial rotation, rotational velocity, X-factor,and X-factor stretch were identified as factors related to driving performance. Although the weighted equipment literature reviewed did not substantiate its use as part of warm-up for performance enhancement, the literature was limited to baseball, warranting further research specifically in golf. The two experimental studies compared the effects of using the SuperSpeed Golf™ weighted clubs and warm-up protocol versus a golf-specific control warm-up protocol in high level amateurgolfers. Although SuperSpeed significantly and meaningfully increased clubhead speedand influenced a subset of swing biomechanics acutely, these changes were no longer meaningful after walkingthe distance of a simulated golf hole. The Royal and Ancient rules of golf prohibit the use of ergogenic aids like the SuperSpeed clubs once tournament play has started. Therefore, the financial, time, and practical value of investing in the SuperSpeed GolfTM weighted clubs product are questionable as might only improve performance on the first hole. Future research is needed to determine the influenceof prior exposure to SuperSpeed GolfTM and of changing the sequence or weights of the clubs on the acute and persistence of potentiation effects.The current experimental studies were laboratory-basedand involved high level amateurs; hence, generalisation to on-course environments and lesser or better-skilled golfers needs confirmation.